Do the elderly and those with comorbid chronic physical conditions have improved access to outpatient psychotherapy post structural reforms in Germany? Results of the ES-RiP study - Jedamzik, Johanna; Kampling, Hanna; Christoffer, Andrea; Szardenings, Carsten; Heuft, Gereon; Friederich, Hans-Christoph; Kruse, Johannes (Frontiers in Psychiatry, 2024)
Background: In 2017, a reform of the German outpatient psychotherapy guideline was carried out, aiming to reduce waiting times and facilitate low-threshold access. This study analyzes the extent to which the implementation of the two new service elements 'psychotherapeutic consultation times' and 'acute short-term psychotherapeutic interventions' improved psychotherapeutic care for patients with mental disorders and chronic physical conditions (cMPs), for patients with mental disorders without chronic physical conditions (MnoP), and elderly patients. Methods: In a quantitative secondary analysis, we analyzed health insurance data of patients with psychotherapy billing codes obtained from the National Association of Statutory Health Insurance Physicians (KBV) for the years 2015-2019, evaluating descriptive statistical parameters for specific patient groups and care services. Results: Between 2015 and 2019, the number of mentally ill receiving psychotherapy at least once in the corresponding year increased by 30.7%. Among these, the proportion of cMPs-patients increased from 26.8% to 28.2% (+1.4%), while that of MnoP-patients decreased from 68.3% to 66.4% (-1.9%). The number of elderly people receiving treatment also increased. Conclusion: Since increases and decreases in the percentage shares occur evenly over the years investigated, it is questionable whether the reform in 2017 has had a direct influence on these changes. Registration: Approval was obtained from the Ethics Committee of the Justus Liebig University Giessen and Marburg -Faculty of Medicine (approval number: AZ 107/20; 6th October 2020).